Genetic Susceptibility to Chagas Disease: An Overview about the Infection and about the Association between Disease and the Immune Response Genes - Ayo, Christiane Maria (Hindawi Publishing Corporation, 2013)
Chagas disease, which is caused by the flagellate parasite Trypanosoma cruzi, affects 8–10 million people in Latin America. The disease is endemic and is characterised by acute and chronic phases that develop in the indeterminate, cardiac, and/or gastrointestinal forms. The immune response during human T. cruzi infection is not completely understood, despite its role in driving the development of distinct clinical manifestations of chronic infection. Polymorphisms in genes involved in the innate and specific immune response are being widely studied in order to clarify their possible role in the occurrence or severity of disease. Here we review the role of classic and nonclassic MHC, KIR, and cytokine host genetic factors on the infection by T. cruzi and the clinical course of Chagas disease.